IMPLEMENTASI MEDIA CANVA DAN QUIZLET PADA PEMBELAJARAN FABEL DI SMP MUHAMMADIYAH PURWOREJO PASCAPANDEMI - Pandan Damayanti; Ani Rakhmawati (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
Current technological developments need to be followed by adaptation to the world of education. However, the problem in the world of education today is that there is still unpreparedness and gaps in the use of technology in the educational sphere. The purpose of this research is as an effort to transform the development of learning media that makes more use of information technology and keeps up with the times. The Canva application can support the learning process because of the many designs provided so that learning materials can be designed more attractively. Then, the Quizlet application provides various features for creating interactive quizzes. This study used a qualitative descriptive method with interview data collection techniques with informants. Based on the results of the research, Canva and Quizlet media for learning fables at SMP Muhammadiyah Purworejo are considered to be very effective. The use of these applications does not make students bored and more interested in learning, so it is hoped that the Canva and Quizlet applications can be used as references or alternatives for teachers in improving student learning outcomes, especially in junior high school students' fable text material